Analysis of Student Academic Resilience: A Study on Coping Stres and Self-Esteem - Yusnaena Yusnaena; Prima Yulianti; Mustika Lukman Arief; Dedi Julianto; Syahrul Effendy (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Final year students are in the age range of 20 to 25 years. These final year students often find conditions that are not pleasant for them because they are in preparation for writing a thesis which they feel is the most challenging and very complicated task. The struggle to compose a thesis is not as easy as working on a report from a particular course. Writing a thesis requires intention, motivation to learn, enthusiasm for learning, hard work, and requires support from the closest people such as family, friends, which in the end, if there is a collision without anyone accompanying it, will cause stress where stress is a condition or condition of a person feeling depressed because of a lot of stress. demands both from within and from outside the individual that must be met. The title of the thesis and the content of the discussion must be in sync or in accordance with the research results. The university strongly demands that students be creative and wise in compiling theses and assignments as an obligation for students sitting on the final level lecture bench. The purpose of this study is to analysis of student academic resilience, a study on coping stres and self-esteem. This type of research is quantitative research. The population in this study was 468 people. Based on the calculation of the formula, the minimum sample of the study amounted to 83 people. This research uses multiple linear regression model. The results showed that coping stress has a positive and significant effect on academic resilience. Self-esteem has a positive and significant effect on academic resilience.